Effects of the Salt-Processing Method on the Pharmacokinetics and Tissue Distribution of Orally Administered Morinda officinalis How. Extract. (11th February 2020) - Shi, Ji; Ren, Xiaohang; Wang, Jia; Wei, Xiaofeng; Liu, Bonan; Jia, Tianzhu
Abstract : Salt processing, which involves steaming with salt water, directs herbs into the kidney channel. After being salt processed, kidney invigorating effects occur. However, the underlying mechanism of this method remains elusive. The compounds monotropein, rubiadin, and rubiadin 1-methyl ether are the major effective components of Morinda officinalis How. To clarify the pharmacokinetics and tissue distribution of these three compounds, we employed liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) to determine the contents of the three components in rat plasma and tissues. Separation was achieved on an Acquity UPLC HSS T3 column (100 mm × 2.1 mm, 1.8 μ m, Waters). Formic acid aqueous solution (0.1%; A) and acetonitrile (containing 0.1% formic acid; B) were used as the mobile phase system with a programmed elution of 0∼5 min with 70% A and then 5∼7 min with 60% A. All analytes were measured with optimized multiple reaction monitoring (MRM) in negative ion mode. Geniposide and 1, 8-dihydroxyanthraquinone were used as the internal standards (IS). The linear ranges were 1.2∼190, 1.3∼510, and 0.047∼37.5 μ g/mL, respectively. Compared with the Morinda officinalis without wood (MO) group, the Cma x and AUC0-t parameters of rubiadin and rubiadin 1-methyl ether elevated remarkably for the salt-processed Morinda officinalis (SMO) groups, which indicates that steaming by salt could increase the bioavailability of rubiadin and rubiadin 1-methyl ether. The T max for monotropein is shorter (0.5 h) in SMO groups than that in MO group, which means that monotropein was quickly absorbed in the SMO extract. Moreover, the contents of three compounds in the small intestine were the highest.